2019
DOI: 10.6026/97320630015506
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition studies of HBV DNA polymerase using seed extracts of Pongamia pinnata

Abstract: Several antiviral compounds for HBV have been identified from traditionally used medicinal plants. We have earlier described the immune modulation properties of P. pinnata, a traditionally used Indian medicinal plant. Therefore, it is of interest to explore the anti-Hepatitis B virus activity of P. pinnata extracts by in-vitro screening assays. This study clearly demonstrated that the 5mg/ml concentration of the aqueous extract significantly inhibited the virus binding. Further, the spectral study was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
(32 reference statements)
2
9
0
Order By: Relevance
“…These promising diverse antiviral bioactions, make chalcone derivatives a favourable broad-spectrum candidate for targeting the most recent viral pandemic, COVID-19 and any other potentially emerging viral diseases. Their interesting biological activities have been studied in several scientific investigations as potential pharmacological agents capable of targeting a variety of human viruses including; MERS-CoV, severe acute respiratory syndromerelated coronavirus (SARS-CoV), HIV, influenza virus, human rhinovirus, herpes simplex virus (HSV), dengue virus (DEN), human cytomegalovirus (HCMV), hepatitis B virus (HBV), hepatitis C virus (HCV), Rift Valley fever (RVF) and Venezuelan equine encephalitis virus (VEEV), through their well discovered antiviral cellular targets and based on specific chalcone skeleton design [20][21][22][23][24][25][26][27][28][29][30]. Figure 1 illustrates the main mechanisms of actions of chalcone derivatives that were reported in literature on different human viruses.…”
Section: Chalcones As Potential Candidates For Treating Viral Infectionsmentioning
confidence: 99%
See 3 more Smart Citations
“…These promising diverse antiviral bioactions, make chalcone derivatives a favourable broad-spectrum candidate for targeting the most recent viral pandemic, COVID-19 and any other potentially emerging viral diseases. Their interesting biological activities have been studied in several scientific investigations as potential pharmacological agents capable of targeting a variety of human viruses including; MERS-CoV, severe acute respiratory syndromerelated coronavirus (SARS-CoV), HIV, influenza virus, human rhinovirus, herpes simplex virus (HSV), dengue virus (DEN), human cytomegalovirus (HCMV), hepatitis B virus (HBV), hepatitis C virus (HCV), Rift Valley fever (RVF) and Venezuelan equine encephalitis virus (VEEV), through their well discovered antiviral cellular targets and based on specific chalcone skeleton design [20][21][22][23][24][25][26][27][28][29][30]. Figure 1 illustrates the main mechanisms of actions of chalcone derivatives that were reported in literature on different human viruses.…”
Section: Chalcones As Potential Candidates For Treating Viral Infectionsmentioning
confidence: 99%
“…Few studies only investigated chalcones role on HBV [28,30]. Patil et al synthesised a group of substituted aryl/heteroaryl derived thienyl chalcones and reported that the more rigid, less bulky thiophenylindenone derivative was the most potent at inhibiting DNA hybridisation in vitro (EC 50 : 4.2 lM; good selectivity index: >24) [30].…”
Section: Chalcone Derivatives Tested On Hepatitis B Virusmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, molecular docking technology was used to screen the active ingredients against HBV, a 3D structure of HBV polymerase (Pol/RT) was modeled and docked with the active compounds, and quercetin ( 18 ) was proved that could enhance its anti-HBV activity up to 10% [ 32 ]. In addition, some researchers found that glabaarachalcone ( 19 ) and isopongachromene ( 20 ), isolated from P. pinnata , could bound with HBV-DNA polymerase protein target [ 33 ]. Isooriention ( 21 ), isolated from S. mussotii , displayed significant anti-HBV activities against the secretions of HBsAg and HBeAg with IC 50 value of 0.79 and 1.12 mM, as well as HBV-DNA replication with IC 50 value of 0.02 mM [ 34 ].…”
Section: The Natural Products Of Anti-hbvmentioning
confidence: 99%